Pengaruh E-WOM Dan Daya Tarik Wisata Terhadap Keputusan Berkunjung Wisatawan Di Kota Lama Semarang - Ray Octafian; Julian Andriani Putri; Dyan Triana Putra; Galih Ahmad Khoiri; Andhara Auror Alnilam; Muhammaad Azhar Putra (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
The Old Town area of Semarang is a tourist destination expected to become an icon of the city. Revitalization efforts carried out by the government between 2020-2023 have successfully made the Old Town area of Semarang more attractive. However, the majority of tourists visiting the area tend to only take photos and sit around without truly enjoying the tourist facilities provided. Therefore, this research aims to identify the influence of attraction and electronic word of mouth on the decision to visit the Old Town area of Semarang. The research method used is explanatory research employing questionnaires, interviews, and literature studies as data collection tools. The population of this research is domestic tourists who have visited the Old Town area of Semarang in the past 3 years and have social media accounts. A sample of 100 respondents was taken using nonprobability sampling methods, particularly purposive sampling approach. The research results indicate that electronic word of mouth and attraction positively contribute to the decision to visit the Old Town area of Semarang.